A Prevalence Study of Canine Humeral Condylar Fractures Over a Ten-Year Period at an Academic Teaching Hospital - Schettler, Michael; Cassel, Nicky; Elliot, Ross C.; Fosgate, Geoffrey T.; Schettler, Keleigh; Biller, David (Veterinary and Comparative Orthopaedics and Traumatology, 2022)
Objective The aim of this study was to investigate the prevalence, breed predisposition and fracture conformation of humeral condylar fractures (HCF) over a 10-year period. Results were compared with published studies emanating from the United Kingdom exploring effect of breed on HCF.Methods Data for all canine admissions to the Veterinary Teaching Hospital at Kansas State University were extracted for the period January 2010 to October 2020. Humeral fractures were recorded and further subclassified as medial, lateral and ‘T’/‘Y’ condylar fractures. The associations between HCF and subtypes with breed were assessed using univariate logistic regression with a comparison group. Multivariable logistic regression was used to evaluate the effect of breed while accounting for dog age, sex and neuter status.Results Of the 44,952 canine patients seen during the study period, period prevalence (95% confidence interval [CI] for HCF was 0.26% [0.22, 0.31]). After adjustment for age and neuter status, French Bulldogs were 49 times more likely to be diagnosed with a HCF compared with the comparison breed group (odds ratio [OR], 49.0; 95% CI, 26.9–89.3). After adjustment for age and neuter status, Cocker Spaniels (OR, 42.8; 95% CI, 16.8–108.6), Boston Terriers (OR, 22.9; 95% CI, 11.0–47.9) and Brittany Spaniels (OR, 21.5; 95% CI, 7.3–63.1) had the next highest increase in HCF compared with the comparison group.Conclusion Based on a study population from the United States, French Bulldogs were 49 times more likely to be diagnosed with a HCF compared with the comparison breed group.
Keywords: humeral condylar fracture; dog; breed; prevalence; French Bulldog